GERAKAN EDUKASI DAN PENYULUHAN PERILAKU PEDULI KEPADA SESAMA BERKOLABORASI DENGAN KOMUNITAS RAWI MATAHO (RM PROJECT) - Tri Sugiarti Ramadhan (Universitas Mataram, 2023)
This community service is carried out in the context of caring for each other on the Moon Ramadhan, which was carried out by the Rawi Mataho Community (RM Project), distribution of iftar menu packages was distributed to people in two different areas, first in Kab. Dompu. West Nusa Tenggara, both of which are in the city of Malang. In East Java, iftar menu packages are given to those who need them, such as cleaners, pedicab drivers, public transport drivers, security guards, street vendors, administrators of mosques or prayer rooms (marbot), and so on. This activity was planned a week earlier by gathering donors and parasponsorship, then distributed with two schemes through fellow members Community RM Project District Kab. Dompu District and Malang City, the final evaluation was carried out and closed with a prayer. The number of packages distributed was 115 iftar menu packages. This activity aims to educate, raise awareness and share fortune. This program will be routinely planned every year to create solidarity among fellow members.